Are you getting it? Integrating theories to explain intentions to get vaccinated against COVID-19 in Spain. Issue 9 (5th October 2022) - Matute, Jorge; Palau-Saumell, Ramon; Meyer, Jan; Derqui, Belén; Jiménez-Asenjo, Noelia
Abstract: Based on the Health-Belief Model, the Theory of Reasoned Action and elements from social exchange, political ideology and fairness theories, this study explores the factors explaining individuals' intentions to be vaccinated against COVID-19. Data were collected from a representative sample of the Spanish population composed of 507 citizens. The proposed model is tested with Partial Least Squares. Empirical testing suggests that attitudes toward the vaccine and moral norms directly determine citizens' behavioral intentions to get vaccinated. These attitudes are mainly explained by perceptions about the benefits and risks associated with the vaccine and, to a lesser extent, by the perceived susceptibility, severity and knowledge of the disease, and each individual's personal health orientation. Contrary to our expectations, perceived social pressures and cues to action do not explain behavioral intentions and attitudes, respectively. The findings from this study also suggest that political ideology indirectly, rather than directly, determines attitudes and behavioral intentions to get vaccinated via increased perceptions of trust and fairness involving the government's decisions regarding the vaccination campaign. Overall, results suggest that reasons for accepting, or rejecting, the vaccine are heterogeneous and more complex than expected. Findings provide relevant insights for policymakers when it comes to designing effective interventions to increase the acceptance of the vaccine and reduce infection rates in the short term.